Broadband Circular Polarizer Based on Plasmon Hybridizations - Hong-Yu Shi; Wei Li; Shi-Tao Zhu; Xiao-Li Dong; An-Xue Zhang; Song Xia; Zhuo Xu (International Journal of Antennas and Propagation)
This paper presents a broadband circular polarizer with a ring/disk cavity structure, which is a broadband application of plasmon hybridizations. The proposed design can convert a linearly polarized wave to a circularly polarized wave from 12.66 GHz to 17.43 GHz within a bandwidth of 30%. The broadband polarization conversion characterization results from the different plasmon hybridization modes induced in the ring/disk cavity. The proposed broadband circular polarizer is demonstrated by both full-wave simulation and measurement.